Heterogeneity and college choice: Latent class modelling for improved policy making. (December 2019) - Schmidt, Alejandro; Ortúzar, Juan de Dios; Paredes, Ricardo D.
Abstract: The huge increase in higher education coverage in many developing countries has gone hand-in-hand with an additional supply of private colleges and with the enrolment of low to middle-class students, previously excluded from a historically elitist education segment. The larger diversity of both "suppliers and consumers", unseen a few years ago, calls for methodological approaches that recognize heterogenous tastes and eventually, to classify individuals into mutually exclusive groups, something that can improve the design of public policy. The importance of college choice in educational systems using voucher schemes, makes it relevant to know what are the main variables determining such choice and whether they differ among different groups. Chile, one of the countries with the most extensive voucher system in education, experienced a significant increase in higher education enrolment (over 250% over the last 15 years), and has faced fierce political controversy due to the high heterogeneity in college quality. We use a latent class choice model to capture differences between groups, an approach that performs significantly better than simpler models previously used in this area. We found that groups of individuals with different selection patterns exist, which could not be defined ex ante, and that those groups are not only differentiated by their income level but mainly, by how they performed at high school. From the different sensitivities to college characteristics such as cost, quality, and location, identifying these groups allows us to derive different policy prescriptions.